A Virtual Reality Environment Using Concepts of Serious Games and Gamification for the Treatment of Eating Disorders - Rodrigues, Francielly; Wilbert, Priscila; da Silva , José Carlos Tavares; de Oliveira , Jauvane C. (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2019: Anais do XIX Simpósio Brasileiro de Computação Aplicada à Saúde, 2019)
An eating disorder is a disturb characterized by an atypical eating behavior. The most common strategy for treatment is CBT, and its limitations have shown to be overcome using virtual reality approaches. Most VR envi- ronments created for this purpose reproduce tasks for treatment of body image disturbances and food avoidance. This work presents a new approach for eating disorders treatment using VR and concepts of serious games and gamification, which have been shown of promising potential in health context due to its ad- vantages when compared to other approaches. Tests assessing the usability and sense of presence in the virtual environment were applied to a group of 10 par- ticipants, indicating that the environment is well suited for medical treatment.